2021
DOI: 10.1039/d1ra04983f
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing polymer-conjugate albumin-based ultrafine gas bubbles in combination with ultra-high frequency radiations in drug transportation and delivery

Abstract: Ultrafine bubbles stabilized by human serum albumin conjugate polyethylene glycol ameliorates the stability of complex as well as the drug payload. Polyethylene glycol presents the crucial role in releasing drug by means of acoustic sound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…It is worth noting that the burst of gas bubbles during high-frequency ultrasound exposure leads to physical damage on the vascular wall, as illustrated in Figure c. The control experiment, however, showed that certain acoustic radiation did not result in significant bubble bursting, enabling the plausibility of using UBs to transport and deliver drugs …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the burst of gas bubbles during high-frequency ultrasound exposure leads to physical damage on the vascular wall, as illustrated in Figure c. The control experiment, however, showed that certain acoustic radiation did not result in significant bubble bursting, enabling the plausibility of using UBs to transport and deliver drugs …”
Section: Results and Discussionmentioning
confidence: 99%
“…The control experiment, however, showed that certain acoustic radiation did not result in significant bubble bursting, enabling the plausibility of using UBs to transport and deliver drugs. 86 Unfortunately, the number of cells that are harmed by one single bubble burst as well as the amount of surrounding liquid subjected to such a high energy remains unknown. In a study by Walls et al on the estimation of the risk that bursting bubbles of various sizes can cause suspended cells, it was indicated that at a constant flow rate, larger relative volumes are damaged by smaller bubbles.…”
Section: Interaction Between Ultrafine Bubbles and Mammalian Cells Di...mentioning
confidence: 99%
“…One of the characteristics of the bubble reagents used in medical applications and research is that they are stabilized by shells composed of various compounds. MB and NB shells can be composed of phospholipids [ 44 , 45 ], polymers [ 46 , 47 ], or proteins such as HSA [ 48 , 49 , 50 , 51 ]. HSA, which consists of three flexible spheres (domains I, II, and III) and two binding sites that provide pockets for small molecules, mainly aromatic dyes (binding site 1) and lipophilic carboxylic acid derivatives (binding site 2) [ 52 , 53 ], is an abundant protein in the human body and is thus highly biocompatible.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin-shell bubbles can also carry pDNA [ 62 , 63 ] and viruses containing integrated genes [ 64 ]. Furthermore, HSA-based bubbles can be PEGylated to improve stability [ 50 ]. In our previous study, we developed albumin-based NBs and investigated their characteristics.…”
Section: Discussionmentioning
confidence: 99%